Slaves, women and homosexuals exploring the hermeneutics of cultural analysis - Webb, William J. (Downers Grove, IL IVP, 2001)
Includes bibliographical references and index.
Keywords: Bible -- hermeneutics; Christianity and culture; Slavery in the Bible; Women in the Bible; Homosexuality in the Bible